Comparison of the Filtration Culture and Multiple Real-Time PCR Examination for Campylobacter spp. From Stool Specimens in Diarrheal Patients - Liang, Hao; Wen, Ziyu; Li, Ying; Duan, Yongxiang; Gu, Yixin; Zhang, Maojun (Frontiers in Microbiology, 2018)
Campylobacter is one of the most common pathogens leading to the bacterial diarrheal illness. In order to set up one effective culture independent assay for the screen of the Campylobacter infection in the diarrheal patients, the quadruple real-time PCR method comparing to the culture based on the enriched filtration method which was recognized as the most effective isolation method was assessed for 190 stool samples from the diarrheal patients collected during the Foodborne Diseases Active Surveillance Network in Beijing. This multiple real-time PCR was designed to identify the Campylobacter genus, C. jejuni, C.coli and C. lari simultaneously. With the enrichment culture method, 23 (12.1%, 23/190) Campylobacter isolates were obtained（19 C. jejuni and 3 C. coi）, however, 31 samples (16.3%, 31/190) were detected positively with the real-time PCR (21 C. jejuni, 8 C. coli and 2 Campylobacter genus only). With the comparison, the real-time-PCR method is more sensitive than the enrichment filtration method (16.3% vs 12.1%, p=0.021). Among the culture-positive samples, 95.7% (22/23) were detected positively by PCR which indicate the specificity of this method was higher. These two methods were consistent well (Kappa=0.785, p<0.05). Comparing to the culture methods, the result of the multiple real-time PCR method is sensitive, reliable and rapid. The present study indicated this multiple real-time PCR can be used both for the surveillance network and the preceding screen for bacteria isolation. This is first comparative study between the culture and multiple real-time PCR method for Campylobacter identification in stool specimens from the diarrheal patients.